Diabetic Patients’ Family’s Health Beliefs Toward Diabetes Prevention and The Contributing Factors - Kurniawan, Titis; Nurfuadah, Irfani; Adiningsih, Dian (Media Keperawatan Indonesia, 2020)
Health beliefs among family members of diabetic patients are important factor of the diabetic preventing behaviours. This study aimed to describe family’s beliefs toward diabetes mellitus prevention based on the Health Belief Model and its’ contributing factors. This corelational study involved 72 peoples that purposively sampled from 34 diabetic patients who live in Jatinangor Public Health Center Working area. A questionnaire developed by the research team consisted of 37 items and 6 domains: perceived susceptibility, severity, benefits, barriers, cues to action, and self efficacy was used to collect the data. The collected data were analyzed descriptively and inferentially. The results showed that most of respondents (77.78%) positively believed on diabetes mellitus (DM) susceptibility, severity (59.72%), benefits of DM prevention (84.77%), and cues to action (76.4%). It was also found that most of respondents negatively believed on the prevention barriers (84%) and self-efficacy (77.78%). Female and actively involved in patient care were found as the contributing factors of the respondents’ beliefs related to DM prevention (p<0.05). To conclude, the DM patients’ family members believed that they are vulnerable to have DM and DM preventions are beneficial. Female and being actively involved in patient care potentially increase the family members’ beliefs toward DM prevention. So, it is important for the healthcare professionals to maximize the family members’ involvement in DM patient care program.